Bioactive compounds and biological functions of medicinal plant-derived extracellular vesicles - Siyu Hao; Hongyu Yang; Jiaojiao Hu; Lili Luo; Yuan Yuan; Libing Liu (Elsevier, 2024)
Extracellular vesicles (EVs) are tiny lipid bilayer-enclosed membrane particles released from a variety of cell types into the surrounding environment. These EVs have massive participated in cell-to-cell communication and interspecies communication. In recent years, plant-derived extracellular vesicles (PDEVs) and "exosome-like" EVs populations found in distinct plants have attracted widespread attention. Especially, research on medicinal plant-derived extracellular vesicles (MPDEVs) are increasing, which are considered a kind of promising natural compound. This review summarizes current knowledge on MPDEVs in terms of bioactive compounds, including small RNA, protein, lipid, and metabolite, have been found on the surface and/or in the lumen of MPDEVs. Moreover, both in vitro and in vivo experiments have shown that MPDEVs exert broad biomedical functions, such as anti-inflammatory, anticancer, antioxidant, modulate microbiota, etc. MPDEVs may be a better substitute than animal-derived extracellular vesicles (ADEVs) because of safety and biocompatibility in the future.